Development and Application of Optical Coherence Tomography (Oct) - Michael Pircher (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This special feature issue has been initiated to celebrate the 25th anniversary of Optical Coherence Tomography (OCT). In OCT, broad bandwidth light is used in order to produce cross sectional images of turbid and translucent samples with high axial resolution (in the order of a few µm). The imaging speed of OCT can be as high as several millions of depth scans (A-scans) per second which allows for various applications in different fields. This special feature issue consists of three overview papers covering OCT angiography, polarization-sensitive OCT and dental applications of OCT. Additional applications and the latest developments in OCT are covered in nine research papers. The latest developments presented in this issue include magnetomotive OCT, resonant Doppler OCT, full field OCT, new segmentation algorithms and depth range extension. Applications of OCT are widely spread and range from quality control in tooth prostheses and coating thickness measurements in the automotive industry to the assessment of degradation of coatings and alveolar dynamics.